Knowledge, attitudes, and practices about Chagas disease in Aguazul, Casanare (Colombia) - Cano-Rodríguez, Leidy Constanza; Orjuela-Vargas, Julie Liliana; Monroy-Díaz, Ángela Liliana (Universidad y Salud, 2021)
Introduction: Chagas disease is caused by the protozoan Trypanosoma cruzi. It is considered a public health problem in Colombia that requires a baseline to face this pathology. Objective: To identify knowledge, attitudes and practices of the inhabitants of the municipality of Aguazul-Casanare to handle Chagas disease. Materials and methods: A descriptive cross-sectional study was conducted on 389 families of the municipality. Sociodemographic and epidemiologic factors as well as knowledge, attitudes and practices were investigated. Results: 221 women (56.8%) and 168 men (43.2) participated in the study. 31.4% and 31.6% of participants have optimal and appropriate knowledge, respectively. Optimal attitudes were observed in 85.9% of people, whereas 56.3% show improper practices, and 43.3% have good and regular practices. Conclusions: Even though, the community has positive attitudes towards prevention of the infection, there is a reduced percentage of people showing optimal knowledge, which is reflected in unhealthy practices. Thus, it is important to establish educational actions aimed at strengthening knowledge related to the Chagas that have an impact on the reduction of this endemic disease.